Home Schooling Sebagai Pendidikan Alternatif - Akhmad Kasinu (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: School s as an educational institution which most people regard as the main institution in educating children today begin to doubt. This institution is deemed not able to optimally to achieve these noble ideas. School educational institutions is felt most people only as an institution that targets only the curriculum, concerned with value and achievement as measured on the basis of ranking, are not concerned with the development potential of children, even more, school is considered as an institution that student creatiivity into it. So these days many parents begin to look to the concept of why home schooling began in great demand. This paper will examine why home schoolong should be used as an alternative model of education to answer the lack of success of the school institution in realizing the ideals of the above. Keywords: Home schooling, Educational Institution.